The Mediating Role of Self-Efficacy and Outcome Expectations in the Relationship Between Peer Context and Academic Engagement: A Social Cognitive Theory Perspective - Getachew Tassew Woreta; Girum Tareke Zewude; Krisztián Józsa (Behavioral Sciences)
Student engagement in learning has well-recognized positive effects on both academic and non-academic aspects of development. However, there has been limited research on the factors that shape it. This study examined the influence of peers’ academic norms, educational aspirations, and effort socialization on students’ academic engagement, placing self-efficacy and outcome expectations as mediators. Grounded in Bandura’s social cognitive theory, data were collected cross-sectionally from 596 high school students (male = 315) in Ethiopia. The results of the path analysis demonstrated a good model-data fit. Peers’ academic norms, educational aspirations, and effort socialization positively predicted academic engagement. Bootstrap analysis with 5000 samples revealed that academic self-efficacy (β = 0.022, BC 95% CI = [0.008, 0.041], p < 0.01) and outcome expectations (β = 0.053, BC 95% CI = [0.028, 0.086], p < 0.001) partially mediated the relationship between peer educational aspirations and students’ academic engagement. The partial mediated effects of peers’ academic norms on academic engagement via self-efficacy (β = 0.030, BC 95% CI = [0.014, 0.054], p < 0.001) and outcome expectations (β = 0.037, BC 95% CI = [0.014, 0.062], p < 0.01) were also significant. Additionally, peer effort socialization showed significant positive indirect effects on academic engagement, mediated by academic self-efficacy (β = 0.024, BC 95% CI = [0.009, 0.044], p < 0.01) and outcome expectations (β = 0.078, BC 95% CI = [0.050, 0.112], p < 0.001). Overall, the mediation analysis revealed that outcome expectations and self-efficacy partially mediated the link between academic engagement and the peer context, highlighting the importance of these mediators in enhancing student engagement.